A Subjective Assessment of the Prevalence and Factors Associated with Poor Sleep Quality Amongst Elite Japanese Athletes - Masako Hoshikawa; Sunao Uchida; Yuichi Hirano (SpringerOpen, 2018)
Abstract Background The amount, quality, and timing of sleep are considered important for athletes' ability to train, maximize training responses, and recover. However, some research has shown that elite athletes do not obtain sufficient sleep. Based on this background, researchers recently started to assess and manage sleep in elite athletes. The purpose of this study was to clarify the prevalence of poor sleep quality and its associated factors amongst elite Japanese athletes. Methods Eight hundred and ninety-one candidates for the 17th Asian Games Incheon 2014, who were over 20 years old, participated in this study. They completed a questionnaire that included the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale, two-question case-finding instruments, and a checklist for sleep hygiene. Data from 817 of the 891 athletes (91.7%) with no missing values were analyzed. Results The mean time in bed was 7 h and 29 min. Two hundred and twenty-nine (28.0%) athletes showed a PSQI global score above the clinical criteria. A multiple logistic analysis revealed that sleep quality was significantly associated with five factors: "time in bed," "eating breakfast every morning," "avoiding the use of electronic devices (PC, smartphone, etc.) just before bedtime," "depressive mood", and "not thinking about troubles while in bed." Forty percent of athletes reported they had been informed by someone about "snoring loudly" and/or "leg twitching or jerking during sleep." Conclusions The results of this study demonstrate that 28% of the athletes showed the PSQI score above the cutoff for poor sleep quality (> 5.5), which suggests that there may be a high prevalence of poor sleep quality in this population of athletes. To improve athletes' sleep, the five factors associated with sleep quality should be emphasized in athletes' sleep education. Furthermore, in medical evaluations of athletes, it may be desirable to include screening for sleep disorders.